Management of hydrocephalus associated with autoimmune diseases: a series of 19 cases - Baitao Ma; Hao Wu; Hexiang Yin; Jianbo Chang; Li Wang; Renzhi Wang; Wenbin Ma; Yongning Li; Jian Guan; Jinjing Liu; Junji Wei (Taylor & Francis Group, 2017)
Objectives: To analyze the diagnosis and treatment of hydrocephalus associated with autoimmune diseases and to explore the possible mechanism of hydrocephalus in these patients. Methods: A retrospective case series study was conducted at Peking Union Medical College Hospital, Beijing, China. Files were retrieved from the hospital archives by screening records from Jan 1990 to Jan 2016. Medical records were screened for data regarding (1) the number of patients diagnosed with hydrocephalus associated with autoimmune diseases, (2) the clinical manifestation of hydrocephalus associated with autoimmune disease, and (3) the outcomes of these patients treated with medication or ventriculoperitoneal shunt (VPS). Results: A total of 19 of 19,643 hospitalized autoimmune diseases patients were found to have hydrocephalus. Seven of the 19 patients had systemic lupus erythematosus (SLE), 3 patients had Sjögren's syndrome, 2 patients had rheumatoid arthritis (RA), 1 patient had connective tissue disease, 1 patient had juvenile idiopathic arthritis (JIA), 1 patient had Guillain-Barre syndrome (GBS), 1 patient had systemic sclerosis, 1 patient had Crohn's disease, 1 patient had relapsing polychondritis (RPC), and 1 patient had autoinflammatory disease (AID). Of the 19 patients, 13 received medication treatment, and the most commonly used drugs were corticosteroids and mannitol. A total of 6 patients received both medication therapy and VPS treatment with a programable valve. After average follow-up lengths of 11 months for patients who received VPS and 8.2 for patients who received medical treatment, the clinical symptoms of patients treated by VPS or medication were improved (83% (5/6) vs. 15.4% (2/13), respectively), patients were in stable condition (17% (1/6) vs. 30.8% (4/13), respectively), and mortality decreased (0% vs. 53.8% (7/13), respectively). Conclusions: VPS along with corticosteroids and immunosuppressants represents an effective treatment approach for patients who suffer from hydrocephalus associated with autoimmune diseases.